Value of phage typing of Vibrio cholerae biotype eltor in West Africa - Bockemühl, J. (1976)
The epidemiological value of phage typing of El Tor vibrios in West Africa was assessed by testing 211 representative strains from all outbreaks of the cholera epidemic in Togo (1970-73) with the prophage typing method of Nicolle et al. and the lytic El Tor phages of Basu & Mukerjee. Prophage typing proved to be of limited epidemiological value in Togo since 203 of the 211 strains tested belonged to the same phage type—namely, type 2 of Nicolle et al., which corresponds to the Celebes type of Takeya. Six strains belonged to type 1, 1 strain to type 4, and 1 strain was untypable. Tested by the lytic El Tor phages, 175 strains were found to belong to type 4 of Basu & Mukerjee, 35 strains to type 1, and 1 strain was untypable. All but two strains of type 1 were isolated from 3 outbreaks in which this phage type was found almost exclusively. The results are in good agreement with epidemiological data collected during the epidemic. El Tor phage V reacted with a specificity of over 99% when tested against 601 strains of El Tor and NCV vibrios from Togo and may be recommended for the rapid identification of El Tor vibrios.